Ammonium supply represses iron limitation to support Symbiodiniaceae growth - Versola, Joshua James N.; Reich, Hannah G.; Rodriguez, Irene B. (Frontiers in Microbiology, 2025)
Nutrient exchanges promote the success of symbioses among reef-building corals, endosymbiotic dinoflagellates (Family: Symbiodiniaceae), and their microbial symbionts. Nutrient dynamics has considerable implications on the metabolism and proliferation of the coral holobiont, with nutrient limitation known to increase the susceptibility of corals to bleaching by disrupting the host-symbiont nutrient exchange. This study examines how two Symbiodiniaceae species, Symbiodinium microadriaticum RT 362 and Cladocopium goreaui RT 152, respond to varying iron (Fe) availability, nitrate (NO3−), and ammonium (NH4+) in batch cultures. Under Fe limitation, phytoplankton growth is reduced when relying on NO₃− due to the higher Fe requirement for nitrate assimilation enzymes, whereas NH4+ uptake is more efficient as it bypasses these Fe-dependent processes. Symbiodiniaceae utilize these nitrogenous compounds to fuel their metabolic processes, with an advantage in using NH4+ due to its greater energy efficiency and lower Fe requirement. Due to its role as cofactor of enzymes, Fe is crucial for nitrate reduction and chlorophyll synthesis, NH4+ assimilation remains effective even under low Fe conditions. The study reveals that in S. microadriaticum and C. goreaui, chlorophyll production, closely linked to Fe availability, and significantly influences carbohydrate and lipid synthesis, with both species boosting protein and carotenoid production under low Fe conditions. Chlorophyll and the other photosynthetic macromolecule product concentrations continue to increase with NH4+ as the N source, even under low Fe conditions. These findings offer critical insights into how these species adapt to varying environmental conditions, improving our understanding of coral resilience.